Consumers perceptions in product quality and the buying decision in the electrical and electronics products in Kota Kinabalu, Sabah / Jumarni Sule - Sule, Jumarni (2012)
The purpose of this research is to investigate the consumers' perceptions on product quality and their buying decision in electrical and electronics products. This study has focused on four variables which are SIRIM Label, Price, Brand Name and Country of Origin. This research also identifies the services offered by SIRIM Berhad and SIRIM OAS International Sdn. Bhd. in term of the quality and standards of products. This research was found that most of the respondents have knowledge about SIRIM Label and has purchased the product that has SIRIM Label before. Most of them also agreed that the product that has SIRIM Label is high quality and affecting their purchase decision compared with the other variables. However, some of the respondents did not have enough information on the label and SIRIM's role as well. This fact has indicated based on the respondents' suggestions and recommendations to SIRIM on strategies to promote good perception on consumers and their buying decision of high quality products. All the data gathered was analyzed in this study and the findings are very useful especially for the consumers and SIRIM Berhad.